The carbon perception gap in actual and ideal carbon footprints across wealth groups - Johanna Köchling; Julia E. Koller; Jana Straßheim; Yannic Rehm; Lucas Chancel; Claudia Diehl; Harald T. Schupp; Britta Renner (Nature Communications)
Abstract Carbon inequality is gaining attention in public discussions surrounding equitable climate policies. It commonly refers to the unequal distribution of individual greenhouse gas emissions, with wealthier individuals contributing disproportionately higher emissions. Little is known about how people perceive the actual carbon footprint distribution across wealth groups and what they would desire as an ideal distribution. Survey data from Germany show awareness of carbon inequality, with respondents recognizing that wealthier individuals emit disproportionately more. Yet, with surprising consensus, all groups, including the wealthy, desired an inverse ideal distribution, with the wealthy having disproportionately smaller carbon footprints. Nonetheless, most perceived their own carbon footprint as far better compared to others in society and within their wealth group. Here, we show a carbon perception gap, particularly among the wealthiest: Collectively, people acknowledge the presence of carbon inequality and desire a more equitable distribution, yet often perceive themselves as already contributing more than others.